Is there a role of whole-body bone scan in patients with esophageal squamous cell carcinoma - Li Shau-Hsuan; Huang Yung-Cheng; Huang Wan-Ting; Lin Wei-Che; Liu Chien-Ting; Tien Wan-Yu; Lu Hung-I (BMC Cancer, 2012)
Abstract Background Correct detection of bone metastases in patients with esophageal squamous cell carcinoma is pivotal for prognosis and selection of an appropriate treatment regimen. Whole-body bone scan for staging is not routinely recommended in patients with esophageal squamous cell carcinoma. The aim of this study was to investigate the role of bone scan in detecting bone metastases in patients with esophageal squamous cell carcinoma. Methods We retrospectively evaluated the radiographic and scintigraphic images of 360 esophageal squamous cell carcinoma patients between 1999 and 2008. Of these 360 patients, 288 patients received bone scan during pretreatment staging, and sensitivity, specificity, positive predictive value, and negative predictive value of bone scan were determined. Of these 360 patients, surgery was performed in 161 patients including 119 patients with preoperative bone scan and 42 patients without preoperative bone scan. Among these 161 patients receiving surgery, 133 patients had stages II + III disease, including 99 patients with preoperative bone scan and 34 patients without preoperative bone scan. Bone recurrence-free survival and overall survival were compared in all 161 patients and 133 stages II + III patients, respectively. Results The diagnostic performance for bone metastasis was as follows: sensitivity, 80%; specificity, 90.1%; positive predictive value, 43.5%; and negative predictive value, 97.9%. In all 161 patients receiving surgery, absence of preoperative bone scan was significantly associated with inferior bone recurrence-free survival (P = 0.009, univariately). In multivariate comparison, absence of preoperative bone scan (P = 0.012, odds ratio: 5.053) represented the independent adverse prognosticator for bone recurrence-free survival. In 133 stages II + III patients receiving surgery, absence of preoperative bone scan was significantly associated with inferior bone recurrence-free survival (P = 0.003, univariately) and overall survival (P = 0.037, univariately). In multivariate comparison, absence of preoperative bone scan was independently associated with inferior bone recurrence-free survival (P = 0.009, odds ratio: 5.832) and overall survival (P = 0.029, odds ratio: 1.603). Conclusions Absence of preoperative bone scan was significantly associated with inferior bone recurrence-free survival, suggesting that whole-body bone scan should be performed before esophagectomy in patients with esophageal squamous cell carcinoma, especially in patients with advanced stages.